On the labour market integration of refugees from Ukraine: A simulation study - Yuliya Kosyakova; Herbert Brücker (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Since the onset of Russia's war against Ukraine, the number of Ukrainian nationals in Germany has risen from 156,000 to 1,240,000. Although many plan to return to Ukraine after the war, the duration of the conflict is leading an increasing number of them to consider staying in Germany for an extended period or permanently. Against this backdrop, this research report simulates various scenarios of labour market integration for Ukrainian refugees, based on the employment trajectories of previous refugees and migrants from the former Soviet Union. The scenarios aim to establish realistic expectations about the progress of labour market integration for Ukrainian refugees and to quantitatively assess the impact of specific factors. However, these conditional scenarios should not be misunderstood as forecasts, as they are based on strong assumptions and do not fully control for many relevant factors. [...] – – Seit Beginn des russischen Angriffskriegs auf die Ukraine ist die Anzahl ukrainischer Staatsangehörigen in Deutschland von 156.000 auf 1.240.000 angestiegen. Obwohl ein erheblicher Teil dieser Menschen nach dem Kriegsende plant, in die Ukraine zurückzukehren, zeigt sich, dass mit zunehmender Kriegsdauer immer mehr einen längeren oder dauerhaften Aufenthalt in Deutschland in Betracht ziehen. Vor diesem Hintergrund simuliert dieser Forschungsbericht verschiedene Szenarien der Arbeitsmarktintegration ukrainischer Geflüchteter. Grundlage bilden die Erwerbsverläufe früherer Geflüchteter in Deutschland sowie von Migrantinnen und Migranten aus der ehemaligen Sowjetunion. Die Szenarien zielen darauf ab, realistische Erwartungen über die Entwicklung der Arbeitsmarktintegration von Geflüchteten aus der Ukraine zu bilden, und die Einflüsse spezifischer Faktoren quantitativ zu analysieren. Diese konditionalen Szenarien sind allerdings nicht als Prognosen misszuverstehen, da sie davon abhängig sind, ob die zugrunde gelegten Annahmen zutreffen und viele relevante Faktoren nicht vollständig berücksichtigt werden können. [...]
Keywords: 330; labor market integration; refugees; Ukraine; employment